Integrating Corporate Social Responsibility in Reforming Trade Union Recognition Process - Siti Suraya Abd Razak; Nik Ahmad Kamal Nik Mahmod; Lee Su Yee; Tan Shen Kian (Asian Academy of Management Journal, 2022)
Employees are one of the most important stakeholders in organisations but their interests are often neglected by employers, particularly from the perspective of trade unionism that plays an essential role in safeguarding employee interests. Currently, the existing legislation has discouraged trade union activities and this has directly deprived the employees of their rights for a better working conditions at the workplace. There is also an evidence of anti-union actions taken by employer in recognition claims in order to prevent collective bargaining with trade unions. Corporate social responsibility (CSR) is an important tool in an organisation where the interests of the stakeholders is sustained. This paper investigates the relationship between employer’s CSR practice and its role in reforming recognition process of trade union in Malaysia. Qualitative research is employed to achieve the objective of this study by way of analysing secondary data and conducting legalistic analysis of the case law and statutes related to the issue. Based on the findings of this study, it is found that trade union recognition process can be reformed through integrating CSR practice in the organisation.